How does consumers' knowledge about the persuasion tactics used in advertising (e.g. fear appeals) influence their psychological and behavioural responses? - Livermore, Rebecca S (2009)
The rate of binge drinking in the United Kingdom still remains high, despite government efforts to warn against the short and long-term dangers. Most governmental advertising uses fear appeals to highlight these dangers but research has shown that consumer knowledge of such persuasion tactics can reduce their effectiveness. This research evaluates the effects of the persuasion knowledge model on consumersʼ responses to governmental fear appeals, specifically across the constructs of the extended parallel process model (EPPM). The study uses a self-report questionnaire to assess perceptions across the ages of 18 to 24 years. Most research on the persuasion knowledge model has focused on persuasion knowledge but this research also evaluated the effects of agent knowledge. The results indicate a clear influence of the persuasion knowledge model on participantsʼ reports of perceived level of threat, perceived efficacy and their subsequent fear control and danger control responses. As expected, an increase in the perceived credibility of the advert and attitudes towards the advert increased participantsʼ levels of fear arousal and perceptions of manipulative intent predicted a decrease in levels of fear arousal. Increases in inferences of manipulative intent also predicted decreases in the perceptions of severity and susceptibility of an injury, while an increase in perceived credibility predicted an increase in perceptions of threat, significantly predicting perceived susceptibility but not severity. Agent knowledge did not, however, predict either of the threat variables. Inferences of manipulative intent and perceived credibility were also predictive of a fear control response, in the direction predicted.